Overexpression of ERBB4 JM-a CYT-1 and CYT-2 isoforms in transgenic mice reveals isoform-specific roles in mammary gland development and carcinogenesis - Wali, Vikram B (Breast Cancer Res, 2014)
INTRODUCTION: Human Epidermal Growth Factor Receptor (ERBB4/HER4) belongs to the Epidermal Growth Factor receptor/ERBB family of receptor tyrosine kinases. While ERBB1, ERBB2 and ERBB3 are often overexpressed or activated in breast cancer, and are oncogenic, the role of ERBB4 in breast cancer is uncertain. Some studies suggest a tumor suppressor role of ERBB4, while other reports suggest an oncogenic potential. Alternative splicing of ERBB4 yields four major protein products, these spliced isoforms differ in the extracellular juxtamembrane domain (JM-a versus JM-b) and cytoplasmic domain (CYT-1 versus CYT-2). Two of these isoforms, JM-a CYT-1 and JM-a CYT-2, are expressed in the mammary gland. Failure to account for isoform-specific functions in previous studies may account for conflicting reports on the role of ERBB4 in breast cancer. METHODS: We have produced mouse mammary tumour virus (MMTV) -ERBB4 transgenic mice to evaluate potential developmental and carcinogenic changes associated with full length (FL) JM-a ERBB4 CYT-1 versus ERBB4 CYT-2. Mammary tissue was isolated from transgenic mice and sibling controls at various developmental stages for whole mount analysis, RNA extraction, and immunohistochemistry. To maintain maximal ERBB4 expression, transgenic mice were bred continuously for a year after which mammary glands were isolated and analyzed. RESULTS: Overexpressing FL CYT-1 isoform resulted in suppression of mammary ductal morphogenesis which was accompanied by decreased number of mammary terminal end buds (TEBs) and Ki-67 positive cells within TEBs, while FL CYT-2 isoform had no effect on ductal growth in pubescent mice. The suppressive ductal phenotype in CYT-1 mice disappeared after mid-pregnancy, and subsequent developmental stages showed no abnormality in mammary gland morphology or function in CYT-1 or CYT-2 transgenic mice. However, sustained expression of FL CYT-1 isoform resulted in formation of neoplastic mammary lesions, suggesting a potential oncogenic function for this isoform. CONCLUSIONS: Together, we present isoform-specific roles of ERBB4 during puberty and early pregnancy, and reveal a novel oncogenic property of CYT-1 ERBB4. The results may be exploited to develop better therapeutic strategies in breast cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13058-014-0501-z) contains supplementary material, which is available to authorized users.